Detection of fungi in blood cultures. - Roberts, G D (1975)
In a retrospective study covering the period January 1972 to June 1974, recovery rates of bacteria and of fungi were generally equivalent with tryptic soy broth, Thiol, thioglycolate, and Columbia broth media (all under vacuum with carbon dioxide and sodium polyanetholesulfonate). An additional biphasic medium consisting of brain heart infusion broth and a brain heart infusion agar slant, which was inoculated only where fungal sepsis was suspected clinically, yielded significantly higher recovery rates of fungi. There were 29 instances of cultures with fungi in both the biphasic and broth media, 80 instances of cultures with fungi only in the biphasic medium, and no instances of fungi only in the broth media. The isolates were as follows: Candida albicans, 74; C. parapsilosis, 20; C. tropicalis, 16; Torulopsis glabrata, 18; Torulopsis sp., 1; Cryptococcus neoformans, 12; C. laurentii, 2; and Histoplasma capsulatum, 16. Despite routine subcultures of the broth media to chocolate blood agar within 24 h of inoculation and after 5 days of incubation, detection of fungemia was significantly improved by the use of a biphasic medium.